Finite-time stabilization and H∞ control for a class of switched nonlinear port-controlled Hamiltonian systems subject to actuator saturation. Issue 16 (November 2020) - Wang, Zi-Ming; Wei, Airong; Zong, Guangdeng; Zhao, Xudong; Li, Hanfeng
Abstract: This paper addresses the problems of finite-time stabilization and H ∞ control for a class of switched port-controlled Hamiltonian (SPCH) systems with actuator saturation (AS). By the energy-based multiple Lyapunov functions (MLFs) method and the mode-dependent average dwell time (MDADT) technique, finite-time stability criterion for unforced SPCH systems with all modes finite-time stable is derived. Further, state feedback strategies and truncation inequality technique are employed to achieve finite-time stabilization of SPCH systems with AS, where each unforced subsystem may be finite-time unstable. Besides, a switching state feedback controller is developed to attenuate the external disturbances for SPCH systems with AS and external disturbances, and new criterion is presented to solve the finite-time H ∞ control problem for the augmented system. Finally, numerical examples are provided to show the effectiveness of the proposed methods.